The level of knowledge of contraindications for physical movement stimulation Turing pregnancy among prenatal course participants - Książek, Piotr (Polish Journal of Public Health, 2010)
Introduction. Signifi cant structural changes are part of everyday life in the NHS. In 1948, when the Labour Party government created the National Health Service (NHS) in the United Kingdom, no one could foresee that due to a growing level of social expectations, the NHS will need so many changes. After sixty years of deep structural changes, the basic rule of the NHS remains the same: to separate insurance companies from contractors. In 2002 British Prime Minister Tony Blair presented a 10-year-long plan for curing and changing the NHS called Shifting the Balance of Power. The main feature of the change has given locally based primary care trusts the role of running the NHS and improving health in their areas. Aim. The aim of this study was to assess the impast of signifi cant structural changes in the organization of the front line staff. Material and methods. The study was performed In 2004 in East Midlands Great Britain. The target group was ‘front line staff’ (nurses and health visitors). Five most representative PCTs were chosen with the help of the Director of Public Health at the Trent Strategic Health Authority. Eight questionnaires were sent to each of the PCT front line staff. Each questionnaire consisted of 16 questions related to PCT effectiveness. Each question was evaluated in a 7-grade-scale where 1 meant very rare [occurrence of a phenomenon], whereas 7 - very frequent. Conclusions. The frontline staff seem not to observe Any particular changes in their everyday performance, after the structure of the NHS has changed. At the same time, they are willing to take on new ideas and demands, and translate them into action.